N-doped TiO2 synthesised via microwave induced photocatalytic on RR4 dye removal under LED light irradiation - M.S. Azami,; W.I. Nawawi,; Ali H. Jawad,; M.A.M. Ishak,; K. Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Nitrogen doped titanium dioxide (N-doped TiO2) was synthesized by microwave using urea as nitrogen sources with commercially available TiO2-P25. The N-doped TiO2 was compared with unmodified TiO2 by carrying out the investigation on its properties using x-ray diffraction (XRD) analysis, Brunauer-Emmett-Teller (BET), Fourier transformed infrared spectroscopy (FTIR) and diffuse reflectance spectroscopy (UV-Vis DRS). The photocatalytic activities of N-doped TiO2 and unmodified TiO2 were studied for photodegradation of reactive red 4 (RR4) under light emitting diode (LED) light irradiation. An active photoresponse under LED light irradiation was observed from N-doped TiO2 with 60 min of time irradiation to complete RR4 color removal while no photocatalytic degradation was observed from unmodified.